Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) dan Student Teams Achievement Division (STAD) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika di Kelas IV SD Negeri Pabuaran 03 - Agustin, Anisa; Rasmitadila; Priyatno, Agus (Karimah Tauhid, 2025)
This research is motivated by the existence of several obstacles in the mathematics learning process, including mathematics learning not using learning models, learning is still dominated by educators, most students think learning mathematics is difficult and boring, and student learning outcomes in mathematics are still low. Based on the problems above, the formulation of the problem in this research is: Is there an influence of using cooperative learning models such as Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) on student learning outcomes in class IV mathematics at SD Negeri Pabuaran 03 for the 2023 school year? /2024?. The aim of this research is to determine the effect of using cooperative learning models such as Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) on student learning outcomes in class IV mathematics at SD Negeri Pabuaran 03. In this research sample. Based on the results of the research conducted, it can be concluded that the cooperative learning model of the Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) types has an influence on student learning outcomes. This can be seen from the research results which show a significant difference between the increase in learning outcomes of experimental class students and control class students. In the experimental class (IVA), an increase in learning outcomes was obtained by 25.6 with an average pretest score = 50.6 and an average posttest score = 76.5. Meanwhile, in the control class (IVB) an increase in learning outcomes was obtained by 17.8 with an average pretest score = 54.3 and an average posttest score = 72.1. This means that the average learning outcomes of the experimental class using the Teams Games Tournament (TGT) type cooperative learning model are better than the average learning outcomes of control class students using the Student Teams Achievement Division (STAD) type cooperative learning model